Automatic Evaluation of Histological Prognostic Factors Using Two Consecutive Convolutional Neural Networks on Kidney Samples. Issue 2 (February 2022) - Marechal, Elise; Jaugey, Adrien; Tarris, Georges; Paindavoine, Michel; Seibel, Jean; Martin, Laurent; Funes de la Vega, Mathilde; Crepin, Thomas; Ducloux, Didier; Zanetta, Gilbert; Felix, Sophie; Bonnot, Pierre Henri; et al.
Visual Abstract: Abstract : Background and objectives: The prognosis of patients undergoing kidney tumor resection or kidney donation is linked to many histologic criteria. These criteria notably include glomerular density, glomerular volume, vascular luminal stenosis, and severity of interstitial fibrosis/tubular atrophy. Automated measurements through a deep-learning approach could save time and provide more precise data. This work aimed to develop a free tool to automatically obtain kidney histologic prognostic features. Design, setting, participants, & measurements: In total, 241 samples of healthy kidney tissue were split into three independent cohorts. The "Training" cohort ( n =65) was used to train two convolutional neural networks: one to detect the cortex and a second to segment the kidney structures. The "Test" cohort ( n =50) assessed their performance by comparing manually outlined regions of interest to predicted ones. The "Application" cohort ( n =126) compared prognostic histologic data obtained manually or through the algorithm on the basis of the combination of the two convolutional neural networks. Results: In the Test cohort, the networks isolated the cortex and segmented the elements of interest with good performances (>90% of the cortex, healthy tubules, glomeruli, and even globally sclerotic glomeruli were detected). In the Application cohort, the expected and predicted prognostic data were significantly correlated. The correlation coefficients r were 0.85 for glomerular volume, 0.51 for glomerular density, 0.75 for interstitial fibrosis, 0.71 for tubular atrophy, and 0.73 for vascular intimal thickness, respectively. The algorithm had a good ability to predict significant (>25%) tubular atrophy and interstitial fibrosis level (receiver operator characteristic curve with an area under the curve, 0.92 and 0.91, respectively) or a significant vascular luminal stenosis (>50%) (area under the curve, 0.85). Conclusion: This freely available tool enables the automated segmentation of kidney tissue to obtain prognostic histologic data in a fast, objective, reliable, and reproducible way.